Zakat Fund Management as Corporate Social Responsibility (CSR) at BPRS Karya Mugi Sentosa: Pengelolaan Dana Zakat Sebagai Corporate Social Responsibility (CSR) Di BPRS Karya Mugi Sentosa - Muh Syaukin Muttaqin; Nurlailah; Susilowati (Journal of Islamic Economics, 2025)
Implementation of Zakat Fund Management as Corporate Social Responsibility at BPRS Karya Mugi Sentosa. The purpose of this study was to determine how zakat funds are managed as Corporate Social Responsibility. The type of research method used is descriptive qualitative. With data collection methods using observation, interviews and documentation. The results of this study indicate that BPRS Karya Mugi Sentosa distributes CSR funds from zakat funds and charity funds. BPRS Karya Mugi Sentosa distributes them through BAZNAS, Yatim Mandiri, Nurul Hayat, and other institutions. BPRS Karya Mugi Sentosa has carried out its obligations as a law-abiding sharia bank, namely in accordance with Law Number 23 of 2011 concerning zakat management and Regulation of the Minister of State-Owned Enterprises No. 4 of 2007, namely 2% of the company's profit must be set aside for PKBL (Partnership and Community Development Program). Scientifically, this research contributes to the discourse on integrating zakat and CSR in Islamic banking. Practically, it offers a strategic model for zakat fund management that can be adopted by other Islamic financial institutions.